Communicative Behavior in Sharing COVID-19 Safety Health Protocols: The Filipino Mothers’ Experience - Visperas, Nikko (Social Sciences and Development Review, 2024)
This study explored the communicative behavior of Filipino mothers in sharing COVID-19 precautions with the members of their respective households. The objectives of this study are also presented in this paper highlighting the process of information sharing, through individuals’ behavior, to their family members. This study utilized qualitative research design through focus interviews anchoring on the concept of Grounded Theory. The informants of this study were selected through a convenience sampling approach – these are five mothers based in Quezon City, Philippines.The study revealed themes highlighting the significance of Barangay Communication in acquiring information; the practice of Personal Hygiene Observation and Vitamin Consumption in preventing/ minimizing COVID-19 contraction; the communicative behavior of mothers, highlighting the importance of Staying indoors instructions, Watching News as a Companion, Conveying COVID Repercussions, and Reading Friends’ Admonition; and Responses and Actions stating the Adherence for Prevention done by their family members.
Keywords: Communication; Behavior; COVID-19; protocols; grounded theory; mothers